Obedience Pressure, Professional Ethics, Attitude of Skepticism and Independence Towards Audit Judgment: Tekanan Ketaatan, Etika Profesi, Sikap Skeptis dan Independensi Terhadap Keputusan Audit - Pratama, Bima Cinintya; Ahmad, Zulfikar Ali; Innayah, Maulida Nurul (Universitas Muhammadiyah Sidoarjo, 2018)
This study investigates the interaction effects of obedience pressure, professional ethics, skepticism attitude, and auditor independence towards audit judgment taken by auditors. Total samples of fifty-four Masters of Accounting and Professional Program in Accounting students were provided with a set of questionnaire to see their perceptions of audit judgments. The sample was conducted by convenience sampling method. Analyses of the data using multiple regression found that obedience pressure, professional ethics, and auditor independence significantly affect audit judgment taken by auditors. While, skepticism attitude was not significantly affect audit judgment. We argue that this was because many of our respondents were not having experience as a real auditor so that they did not have audit knowledge well enough that may affect their judgments.